ANALISIS METODE OUTDOOR LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SIWA PADA MATA PELAJARAN KESENIAN KELAS III MI MA’HAD AL-ZAYTUN - Anisa Fitriani; Dede Indra Setiabudi; Dewi Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the Outdoor Learning method in art education for third-grade students at MI Ma’had Al-Zaytun to enhance critical thinking skills. Outdoor Learning integrates the surrounding environment as a contextual learning medium, offering authentic and multisensory experiences. A descriptive qualitative approach was employed, utilizing observation, interviews, and documentation as data collection techniques. The participants consisted of two teachers and six third-grade students selected purposively. The findings reveal that Outdoor Learning effectively improves students’ critical thinking skills through activities such as observation, analysis, reflection, discussion, and creative expression in art projects. Beyond cognitive gains, students also benefited socially and emotionally by developing collaboration, communication, and self-confidence. However, several challenges were identified, including unpredictable weather, limited facilities, and classroom management in outdoor settings. Despite these obstacles, supporting factors such as the school’s natural environment, students’ enthusiasm, and teachers’ active facilitation contributed significantly to the success of the method. Overall, the study concludes that Outdoor Learning is a relevant and effective instructional approach in art education to foster 21st-century competencies, particularly critical thinking. Keywords: Outdoor Learning, Critical Thinking, Art Education, Elementary School